Chelerythrine induced cell death through ROS-dependent ER stress in human prostate cancer cells - Wu S (OncoTargets and Therapy, 2018)
Songjiang Wu, Yanying Yang, Feiping Li, Lifu Huang, Zihua Han, Guanfu Wang, Hongyuan Yu, Haiping Li Department of Urology, Enze Hospital of Taizhou Enze Medical Center (Group), Taizhou, China Introduction: Prostate cancer is the most common noncutaneous cancer and the second leading cause of cancer-related mortality worldwide and the third in USA in 2017. Chelerythrine (CHE), a naturalbenzo[c]phenanthridine alkaloid, formerly identified as a protein kinase C inhibitor, has also shown anticancer effect through a number of mechanisms. Herein, effect and mechanism of the CHE-induced apoptosis via reactive oxygen species (ROS)-mediated endoplasmic reticulum (ER) stress in prostate cancer cells were studied for the first time. Methods: In our present study, we investigated whether CHE induced cell viability decrease, colony formation inhibition, and apoptosis in a dose-dependent manner in PC-3 cells. In addition, we showed that CHE increases intracellular ROS and leads to ROS-dependent ER stress and cell apoptosis. Results: Pre-treatment with N-acetyl cysteine, an ROS scavenger, totally reversed the CHE-induced cancer cell apoptosis as well as ER stress activation, suggesting that the ROS generation was responsible for the anticancer effects of CHE. Conclusion: Taken together, our findings support one of the anticancer mechanisms by which CHE increased ROS accumulation in prostate cancer cells, thereby leading to ER stress and caused intrinsic apoptotic signaling. The study reveals that CHE could be a potential candidate for application in the treatment of prostate cancer. Keywords: chelerythrine, reactive oxygen species, endoplasmic reticulum stress, apoptosis, prostate cancer